Lens Aquaporins in Health and Disease: Location is Everything! - Schey, Kevin L.; Gletten, Romell B.; O’Neale, Carla V. T.; Wang, Zhen; Petrova, Rosica S.; Donaldson, Paul J. (Frontiers in Physiology, 2022)
Cataract and presbyopia are the leading cause of vision loss and impaired vision, respectively, worldwide. Changes in lens biochemistry and physiology with age are responsible for vision impairment, yet the specific molecular changes that underpin such changes are not entirely understood. In order to preserve transparency over decades of life, the lens establishes and maintains a microcirculation system (MCS) that, through spatially localized ion pumps, induces circulation of water and nutrients into (influx) and metabolites out of (outflow and efflux) the lens. Aquaporins (AQPs) are predicted to play important roles in the establishment and maintenance of local and global water flow throughout the lens. This review discusses the structure and function of lens AQPs and, importantly, their spatial localization that is likely key to proper water flow through the MCS. Moreover, age-related changes are detailed and their predicted effects on the MCS are discussed leading to an updated MCS model. Lastly, the potential therapeutic targeting of AQPs for prevention or treatment of cataract and presbyopia is discussed.